2019
DOI: 10.1038/s41586-019-1765-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to mosaic Y chromosome loss in blood

Abstract: Mosaic loss of chromosome Y (LOY) in circulating white blood cells is the most common form of clonal mosaicism 1-5 , yet our knowledge of the causes and consequences of this is limited. Using a newly developed approach, we estimate that 20% of the UK Biobank male population (N=205,011) has detectable LOY. We identify 156 autosomal genetic determinants of LOY, which we replicate in 757,114 men of European and Japanese ancestry. These loci highlight genes involved in cell-cycle regulation, cancer susceptibility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
387
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(422 citation statements)
references
References 90 publications
32
387
0
3
Order By: Relevance
“…The molecular mechanisms behind the association of LOY, aging and neoplasia are not completely understood. There is no clear association between LOY and numerical abnormalities of other chromosomes 9,27,53 . LOY does not seem to reflect an overall propensity for loss of small-sized chromosomes 60,61 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The molecular mechanisms behind the association of LOY, aging and neoplasia are not completely understood. There is no clear association between LOY and numerical abnormalities of other chromosomes 9,27,53 . LOY does not seem to reflect an overall propensity for loss of small-sized chromosomes 60,61 .…”
Section: Discussionmentioning
confidence: 97%
“…Recently, large genome-wide association studies enrolling >200,000 men in the UK Biobank demonstrated association of germline single nucleotide polymorphisms (SNP) of 156 autosomal loci as well as differential methylation of various genes with LOY 4,[25][26][27] . Whether any of the LOYassociated SNPs or epigenetic changes contribute to hematological neoplasia risk is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The current analyses were extension of our previous studies 5,13,14 which included population-based data from 223,336 males between age 37 and 73 recruited between 2007 to 2010 from the UK Biobank 15,16 . After providing informed consent, each participant provided a blood sample, answered a detailed health and lifestyle questionnaire, and had physical measurements taken.…”
Section: Methodsmentioning
confidence: 99%
“…Men with mLRR > 0.15 could possibly have a mosaic gain of Y chromosome or a constitutional extra copy of the Y chromosome (XYY syndrome) and were removed (205 men, 0.09%). We also apply the methods proposed by Thompson et al 14 to call dichotomized mLOY. For clarity, we use the term mLOY for dichotomized mLOY calls by Thompson et al Our final analytical set included 206,353 self-reported men who reported no prior cancer history at recruitment (n = 14,356 excluded), did not have X chromosome heterozygosity (n = 167 excluded), had consistent smoking data (n = 2 excluded), were without evidence of copy number gains of Y chromosome (n = 205 excluded) and passed quality control during the dichotomized mLOY detection step (n = 2,394 excluded) as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…LOY is an age related phenomenon that has been associated with a wide spectrum of human diseases including cancer, Alzheimer's disease, cardiovascular disease, and reduced overall life expectancy in men. [11][12][13][14] Genetic variation in multiple loci is involved in the inherited susceptibility to LOY, which can also be driven by smoking and other environmental exposures. 15 LOY is the most common copy number alteration in male leukocytes, estimated to occur in <2% men under 60 years of age, but exponentially increasing with aging to 15-40% in 70-85 year-old males and >50% at 93 years of age.…”
Section: Introductionmentioning
confidence: 99%